Nocardia Brain Abscess in an Immunocompetent Patient - Kim, Suyoung (The Korean Society of Infectious Diseases and Korean Society for Chemotherapy, 2014)
Nocardia cerebral abscess is rare, constituting approximately 1-2% of all cerebral abscesses. Mortality for a cerebral abscess of Nocardia is three times higher than that of other bacterial cerebral abscesses, therefore, early diagnosis and therapy is important. Nocardia cerebral abscess is generally occur among immunocompromised patients, and critical infection in immunocompetent patients is extremely rare. We report on a case of a brain abscess by Nocardia farcinica in an immunocompetent patient who received treatment with surgery and antibiotics. This is the second case of a brain abscess caused by N. farcinica in an immunocompetent patient in Korea.